THE INFLUENCE OF COMPENSATION, WORK ENVIRONMENT AND LEADERSHIP STYLE ON LOYALTY ASN WORK IN THE ENVIRONMENTAL SERVICES LIVING AND HYGIENE (DLHK) LHOKSEUMAWE CITY - Dinda Wardani; Nurmala; Em. Yusuf Iis; Sullaida (RADJA PUBLIKA, 2024)
The research aims to see the influence of Compensation, Work Environment and Leadership Style on Work Loyalty of Asn in the Department of Environment and Hygiene (DLHK)Lhokseumawe City. The research used primary data obtained from the results of a questionnaire in the form of questions distributed to 40 respondents, namely ASN at the Lhokseumawe City Environment and Hygiene Service (DLHK). The data analysis method used is the multiple linear regression method with the help of SPSS software. The results of this research are that compensation has a positive and significant influence on ASN loyalty. This means that compensation can influence loyalty in the Lhokseumawe City Environmental Service. The work environment has a positive and significant influence on ASN loyalty. This means that the work environment can influence loyalty in the Lhokseumawe City Environmental Service. Leadership Style has a positive and significant influence on ASN loyalty. This means that Leadership Style can influence Loyalty in the Lhokseumawe City Environmental Service. In this way, the Lhokseumawe City Environment and Cleanliness Service improves welfare, work environment, leadership style so that employee work loyalty increases.